Spatial–Temporal Changes and Driving Mechanisms of Ecological Environmental Quality in the Qinghai–Tibet Plateau, China - Zhan Shen; Jian Gong (Land)
This study examines the evolution of eco-environmental quality and its driving forces in the Qinghai-Tibet Plateau, with a particular focus on the Qinghai Lake region (QLR). By employing principal component analysis (PCA) on nearly 20 years of remote sensing data, we reveal the dynamic characteristics of ecological quality in this sensitive area. The results indicate that the ecological quality of the QLR has exhibited significant fluctuations over the past two decades, influenced by multiple factors such as climate change, human activities, and policy adjustments. Specifically, the fluctuations in ecological quality are closely associated with key ecological indicators, including the Normalized Difference Vegetation Index (NDVI), Land Surface Temperature (LST), Wetness Index (WET), and Normalized Differential Bare Soil Index (NDBSI). Vegetation cover and moderate humidity have substantial positive effects on ecological quality, while high temperatures and dry soil conditions exert negative impacts.